Arthropod Predation by a Specialist Seed Predator, the Golden-backed Uacari (Cacajao melanocephalus ouakary, Pitheciidae) in Brazilian Amazonia - Barnett, Adrian Ashton; Ronchi-Teles, Beatriz; Almeida, Thais; Deveny, Adrian J.; Schiel-Baracuhy, V.; Souza-Silva, W.; Spironello, Wilson Roberto; Ross, Caroline; MacLarnon, Ann M. (International Journal of Primatology, 2013)
Morphological adaptations related to food processing generally reflect those elements of the diet that represent the greatest biomechanical challenge or that numerically dominate the diet. However, in periods of the annual cycle when the availability of such foods is low, items to which a species has low apparent morphological adaptation may be included in the diet. Here we test the responses of a diet-specialist primate to limitations in the supply of the resource it is specialized to exploit. Uacaris are primarily predators of immature seeds, in seasonally flooded forests in Amazonian Brazil, and have dental specializations to open hard-shelled fruits. We investigated the importance of arthropods in the diet of golden-backed uacaris (Cacajao melanocephalus ouakary), examining their seasonal importance in the uacari diet, and the ways C. m. ouakary used to access them. Using scan and ad libitum sampling of feeding and phenology from botanical study plots to assess fruit availability, we conducted an 18-mo study in Jaú National Park, Amazonas State, Brazil. We recorded arthropod predation 298 times, with Cacajao melanocephalus ouakary feeding on 26 invertebrate taxa in ≥11 families and 9 different orders. Uacaris extracted wood-boring beetles dentally from rotting wood and smaller larvae from twigs, stems, and petioles, but this food class did not predominate. This food class (encapsulated foods) constituted 23.4 % of the arthropod records. The majority of arthropod food items were either manually removed from substrates (ants, beetle larvae, caterpillars, fulgorid bugs, grasshoppers, mayflies, spiders, termites, wasps, and a whip-scorpion) or plucked from the air (volant Lepidoptera). Uacaris appeared to avoid toxic caterpillars. Insectivory was most frequent when fruit and seeds were least available. Arthropods seem to be seasonally important to this primate, supplementing or making up for shortfalls in the hard fruits and immature seeds for which uacaris have highly developed dental, and possibly intestinal, adaptations. © 2013 Springer Science+Business Media New York.
Keywords: Adaptation; Arthropod; Food Availability; Food Processing; Insectivory; Morphology; Neotropical Region; Primate; Seed Predation; Specialist; Amazonas; Jau National Park; Araneae; Arthropoda; Cacajao Melanocephalus; Caelifera; Coleoptera; Ephemeroptera; Formicidae; Fulgoridae; Invertebrata; Isoptera; Lepidoptera; Pitheciidae; Primates; Scorpiones; Uropygi